The illustrated world encyclopedia of guns : pistols, rifles, revolvers, machine and submachine firearms through history in over 1100 photographs - Fowler, Will, 1947-; North, Anthony, 1942-2012; Stronge, Charles; Sweeney, Patrick, 1953- (London : Lorenz Books, 2015)
GENERAL ENCYCLOPAEDIAS. An authoritative historical guide to the world of military, antique and law-enforcement firearms, photographed throughout.
Includes index.
Keywords: Firearms -- Encyclopedias; Firearms -- History